BASAHAN WEDDING CEREMONY IN SOLO, CENTRAL JAVA - Purwanti Handayaningsih (Conscientia, 2020)
In this article, the writer wants to observe and learn about the wedding ceremony in Solo, Central Java called Basahan. The main objective of this article is to know the symbolic meaning of Basahan clothes and procession so readers can understand about the meanings which contain in this wedding ceremony. This article also purposes to preserve some local wisdoms especially which comes from Java such as lamaran (proposal), srah-srahan (giving some presents to the bride woman), sangat (finding the lucky day), etc. The writer used observation method in collecting data. Besides, some interviews were held to get more data authentically from a resource who knew about the symbolic meaning of Basahan clothes and Basahan procession.The writer also did library research to get some references about symbolic meanings of Basahan clothes and procession. From the observation, the writer found many symbolic meanings in the procession and Basahan clothes which are worn by the bridegroom such as kampuh (a cloth which has animal and plant motif), semekan (cloth which is used as a breast cover for woman), kuluk mathak (Javanese cover head which is worn by the groom), keris ladrang (Javanese traditional weapon). Basically, those symbolic meanings might affect the bridegroom’s life.